Energy and carbon footprints for irrigation water in the lower Indus basin in Pakistan, comparing water supply by gravity fed canal networks and groundwater pumping. (1st March 2021) - Siyal, A.W.; Gerbens-Leenes, P.W.; Nonhebel, S.
Abstract: Irrigation water can come from surface water or groundwater, or a combination of the two. In general, efforts to provide one type or the other differ depending on local circumstances. This study aims to compare energy and carbon footprints of irrigation water provided by either a gravity-fed irrigation network requiring maintenance or a groundwater pumping system. The case study area is the lower Indus basin in Pakistan. For the assessment, the study could make use of data from local governmental organizations. Energy footprints of surface water are 3–4 KJ/m 3, carbon footprints 0.22–0.30 g/m 3 . Groundwater has energy footprints of 2100 for diesel to 4000 KJ/m 3 for electric pumps and carbon footprints of 156 for diesel and 385 g/m 3 for electric pumps. Although groundwater contributes only 6% to total irrigation water supply in the lower Indus basin, it dominates energy use and CO2 emissions. The total energy footprint of surface water in Pakistan is 0.5 10 3  TJ/y, and for groundwater 200 10 3  TJ/y or 4.3% of national energy use. The total carbon footprint of surface water is 36 10 6  kg/y, and for groundwater 16 000 10 6  kg/y or 9% of Pakistan's total CO2 emissions. Although the contributions of water supply to total energy use and CO2 emissions are small, they could increase if more groundwater is used. A shift from groundwater pumping to properly maintaining gravity-fed canal systems decreases energy use and CO2 emissions by 31–82% and increases surface water availability by 3%–10%. Highlights: Canal maintenance with better irrigation supply results in water, energy and carbon savings. Irrigation accounts for 4% of the Pakistan's total energy use and 9% of its CO2 emissions. Water and energy saving potentials in Sindh are 3–10% and 31–82% respectively. Groundwater makes up 6% of irrigation water in Sindh but accounts for 99% of irrigation-related CO2 emissions.